Preferences for the shared use of electric-powered vehicles in mobility packages: an empirical analysis of MaaS in a university context - Decker, Lea; Marx, Christian P.; Weiβ, Matthias; Werbeck, Nicola (Frontiers in Environmental Economics, 2023)
Previous research on preferences of potential Mobility-as-a-Service (MaaS) users often included public transport (PT) in bundled mobility options. Due to the often reported enormous importance of PT availability, including PT in the bundles may have led to distortions in the identification of other vehicle preferences in MaaS offerings. Our analysis counteracts this distortion and investigates how other means of transport are evaluated in mobility packages when PT is not part of the bundle. We included electric-powered mobility alternatives, which have rarely been considered in previous research, to find out which alternatives to PT users would prefer that might increase their approval of MaaS. Furthermore, the results of the existing literature are inconsistent in emphasizing whether sustainability and environmental protection are actually relevant in the valuation of different mobility options. Our analysis thus aims at identifying which electric vehicles are preferred in a mobility package, when PT is not included. We further investigate whether sustainability components of a mobility package influence the preference, structure of individuals. We based the empirical evaluation on a rank-ordered conjoint analysis, in which mobility packages were evaluated according to individual user preferences, including emissions savings. We therefore conducted a study to identify vehicle preferences other than PT and the valuation of sustainability aspects in mobility patterns. We surveyed 995 students to identify preferences and willingness to pay (WTP) for MaaS among this specific user group. Results of the empirical analysis show that preferences for an e-car and an e-scooter exist. Furthermore, we found that sustainability plays a role in the evaluation of mobility packages. Accordingly, we found, that a potential reduction in emissions leads to a higher approval of MaaS. Thus, the study extends the theoretical and empirical understanding of preference-ordering of MaaS packages and clarifies the importance of sustainability in transport choices.